Effects of an Emotional Competence Development Program on University Students with High Scores in the Antagonistic Personality Trait - Montalvo-Garcia, Adolfo; Martí-Ripoll, Margarita; Gallifa, Josep; Ávila-Vila, Santiago (Revista Electrónica Educare, 2023)
Objective. This study aims to understand the effects of an eight-workshop self-leadership program using an experiential learning approach on master’s students with high antagonistic personality traits scores. The study seeks to examine, more comprehensively, the impact of incorporating emotional competence development into a restricted technical competence approach, as a method to facilitate antagonistic students to develop prosocial leadership styles. Methodology. The quasi-experimental ex post facto design (n=126) study implemented self-reported instruments, including the Bisquerra and Pérez-Escoda for the Emotional Competences questionnaire (QDE_A35) and the agreeableness-antagonism sub-scale of the Big Five. Results. The ANCOVA tests revealed significant changes in antagonistic students who attended the self-leadership program (experimental group) compared to those who did not and formed part of the control group. Specifically, the experimental group showed changes in total emotional competence, as well as in the sub-dimensions of emotional awareness, emotional regulation, and emotional autonomy. However, no differences were reported in social competencies and emotional well-being. Conclusion. The self-leadership program analyzed in this study contributes to the development of emotional competence in students with high scores in antagonism.